The role of intellectual humility leadership on thriving at work and performance of new generation employees - Gao, Changchun; Niu, Aiwen; Yu, Chenhui (Frontiers in Psychology, 2025)
BackgroundAs career maturity and self-awareness increase among new-generation employees, they seek not only material rewards but also well-being and meaningful work.MethodsDrawing on Job Demands–Resources (JD-R) theory and Social Exchange Theory (SET), this study establishes a moderated mediation model to examine how intellectual humility leadership influences thriving at work and job performance, with positive job attitudes as a mediator and core self-evaluation (CSE) as a moderator. Data from 518 manager–subordinate dyads in Chinese SMEs were analyzed using structural equation modeling (SEM).ResultsThe findings show that intellectual humility leadership enhances thriving and performance by fostering positive job attitudes, which mediate these effects. Moreover, CSE moderates this relationship: the positive effect of intellectual humility leadership on attitudes is stronger when CSE is high and weaker when it is low.ConclusionThe study contributes theoretically by identifying intellectual humility leadership as a critical job resource and relational signal, refining JD-R and SET, and highlighting generational variations in leadership effectiveness. Practically, it suggests cultivating intellectual humility in leadership development to strengthen engagement, performance, and well-being among Millennials and Gen Z. Limitations include the SME focus and survey design; future research should test additional mediators and adopt longitudinal or mixed-method approaches.